The effect of environmental moisture conditions on the calculated incident radiant heat flux by plate thermometers - Lahiru Jayathunga-Mudiyanselage; Haejun Park; Virginia Charter; Rob Agnew (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study investigates the effect of environmental moisture conditions on the calculated incident radiant heat flux (irradiance) by plate thermometers (PT). Alterations were made to the moisture content of the PT insulation layers to achieve these conditions. Irradiance was calculated using a pre-determined equation based on fully insulated conditions and validated using a Schmidt-Boelter radiometer. The study consisted of two phases; (i) investigating the effect of preheating PT to the accurate irradiance, (ii) investigating the effect of moisture in the PT on the measurement of irradiance. Calculated irradiance agreed with measured for preheated PT, but not with unheated PT. Four representative moisture conditions were identified for phase two, whereby samples were equilibrated at 0, 45, 65, and 98 wood moisture equivalent (%WME). No noticeable difference identified between measured and calculated irradiance was detected within 0-65%WME. PT with 98%WME showed a difference between the irradiance as the moisture inside the PT insulation absorbed energy from the PT to vaporize. Therefore, using preheated PT with any %WME under 65 is recommended to obtain accurate enough irradiance measurements. The result can use to improve determining the fire spread mechanisms and accurate measurements of irradiance in outdoor fires such as informal settlements fires.
Keywords: 650; incident radiant heat flux; moisture content; plate thermometer; fire test